Testing a Model of Organizational Response to Social and Political Issues - Greening, Daniel W.; Gray, Barbara (Academy of Management Journal, 1994)
This study developed and tested a conceptual model explaining variability in the organizational structures firms develop to identify, analyze, and respond to their social and political environments. Institutional and resource dependence theories offer plausible explanations for these structural differences; we tested both, finding that those explanations are distinct but complementary. Issues management is both an institutional response and a strategic adaptation to external pressures. But contrary to our predictions, each theory provided only a partial explanation by accounting for particular responses. Institutional constraints appeared to limit managerial discretion over corporate social responses. We propose a new contingency model of corporate social performance based on these findings.